2021
DOI: 10.1007/s41109-021-00434-y
|View full text |Cite
|
Sign up to set email alerts
|

Testing biological network motif significance with exponential random graph models

Abstract: Analysis of the structure of biological networks often uses statistical tests to establish the over-representation of motifs, which are thought to be important building blocks of such networks, related to their biological functions. However, there is disagreement as to the statistical significance of these motifs, and there are potential problems with standard methods for estimating this significance. Exponential random graph models (ERGMs) are a class of statistical model that can overcome some of the shortco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 135 publications
(217 reference statements)
0
2
0
Order By: Relevance
“…The model helped answer questions about the existence of patterns in the network including whether or not the network exhibited the characteristic of homophily and how organizations should understand their role in the network (Williams and Hristov (2018)). In the biological world, Stivala et al show that ERGM can address some of the limitations that previous research had found in modeling biological processes (Stivala and Lomi (2021)). These examples show the incredible flexibility and significance of exponential random graph models.…”
Section: Examples and Contextmentioning
confidence: 99%
“…The model helped answer questions about the existence of patterns in the network including whether or not the network exhibited the characteristic of homophily and how organizations should understand their role in the network (Williams and Hristov (2018)). In the biological world, Stivala et al show that ERGM can address some of the limitations that previous research had found in modeling biological processes (Stivala and Lomi (2021)). These examples show the incredible flexibility and significance of exponential random graph models.…”
Section: Examples and Contextmentioning
confidence: 99%
“…They are represented in Fig. 1 b. Triadic and tetradic connections are known as the building blocks of complex networks 45 , playing the role of functional modules or evolutionary signs in biological networks 46 , 47 , homophily-driven connections in social networks 48 , complementarity-driven structures in production networks 33 , 36 , their change in time being interpreted as self-organizing processes in the World Trade Web (WTW) 49 , 50 , and early-warning signals of topological collapse in inter-bank networks 51 , 52 and stock market networks 42 . It has been proven that for the majority of (available) real-world networks, the triadic structure is maximally random 53 and by fixing it their global structure is statistically determined 54 .…”
mentioning
confidence: 99%